Studi Etnografi Virtual terhadap Gaya Bahasa Sarkasme Pemain Mobile Legends pada Komunitas Team RRQ Official di Discord - Putri, Dea Rahmanda; Achmad, Zainal Abidin (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2026)
This study investigates the use of sarcastic language by Mobile Legends players in the Team RRQ Official Discord community and its effects on social interaction. Employing a qualitative virtual ethnography method, data were gathered through participant observation and in-depth interviews with eight active members. The study applies Gorys Keraf’s theory of sarcasm and Johanna Maren Hjelle Olsen Olsen’s indicators such as self-contradiction, hyperbolic combinations, sentimental contradiction, and manner violation. A total of 41 sarcastic utterances were found, dominated by irony over mockery. Sarcasm was used to express critique, disappointment, or humor, but also triggered emotional tension and conflict. The findings reveal that sarcasm is not merely spontaneous expression, but a deliberate communicative strategy within competitive virtual communities.